2014
DOI: 10.1016/j.ijporl.2014.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of gel-forming mucins to pathogenic middle ear bacteria

Abstract: Objective To assess the differential response of the secretory gel forming mucins (GFM) to the most common bacterial pathogens causing otitis media, Streptococcus pneumoniae (SP), nontypeable Haemophilus influenza (NTHi), and Moraxella catarrhalis (Mcat), in a culture model of human middle ear epithelium (HMEEC). Methods In vitro cultured HMEEC was exposed to 5µg/ml of bacterial whole cell lysate (WCL). RNA was extracted to generate cDNA. The expression levels of each of the targeted mucin transcripts, MUC2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…More than 20 human (MUC) and mouse (Muc) genes have been identified, with MUC5AC and MUC5B mucins being the predominant polymeric mucin glycoproteins in human airway mucus secretions. Although MUC5B protein has been postulated to be the most abundant mucin in chronic otitis media, [8][9][10][11] MUC5AC has also been identified at the RNA level in middle ear epithelium at baseline [12][13][14] and following bacterial exposure. [15][16][17][18][19] In comparison with MUC5AC, MUC5B regulation in middle ear responses is markedly understudied.…”
mentioning
confidence: 99%
“…More than 20 human (MUC) and mouse (Muc) genes have been identified, with MUC5AC and MUC5B mucins being the predominant polymeric mucin glycoproteins in human airway mucus secretions. Although MUC5B protein has been postulated to be the most abundant mucin in chronic otitis media, [8][9][10][11] MUC5AC has also been identified at the RNA level in middle ear epithelium at baseline [12][13][14] and following bacterial exposure. [15][16][17][18][19] In comparison with MUC5AC, MUC5B regulation in middle ear responses is markedly understudied.…”
mentioning
confidence: 99%
“…Coculture of HMEEC-1 with live SP also demonstrated an induction of MUC5AC mRNA and promoter [126]. Kerschner et al [120] extended the study to other mucins in this cell type: they found mRNA induction of MUC5AC, MUC5B, and MUC2, this being more relevant with the clinical observations of mucins in the middle ear of patients with OM. None of these studies analyzed the mucin proteins.…”
Section: Infection Of the Middle Ear By Bacteria Induces Mucin Producmentioning
confidence: 79%
“…In vitro experiments have been conducted to analyze the mucoid effect of live or lysed bacteria on HMEEsCs-1. The exposure to NTHi, SP, or MC revealed a potency of the HMEEsC-1 to activate the promoter of MUC5AC and the transcription of its mRNA [113,[120][121][122][123][124][125]. Coculture of HMEEC-1 with live SP also demonstrated an induction of MUC5AC mRNA and promoter [126].…”
Section: Infection Of the Middle Ear By Bacteria Induces Mucin Producmentioning
confidence: 94%
“…As we have discussed previously, it is also important to examine the impact of inflammatory responses on a variety of gel‐forming or secretory mucins, which include both MUC5AC and MUC2 . In experiments conducted in our laboratory and elsewhere, each of the GFMs have been demonstrated to have upregulation in the presence of generalized inflammatory agents TNF‐α and IL‐1β, as well as in more specific inflammatory experiments using specific pathogens . The precise function and role of these GFMs in response to various stimuli has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…MUC2 and MUC5AC are produced by goblet and basal cells of surface epithelium, whereas MUC5B and MUC19 are glandular mucins detected mainly in submucosal glands. Studies have demonstrated each of these mucins to be upregulated by proinflammatory cytokines and major pathogenic middle ear bacteria . Among these, MUC2 , MUC5AC, and MUC5B upregulation were demonstrated in middle ear mucosa of children with OM, suggesting their critical roles in OM pathogenesis …”
Section: Introductionmentioning
confidence: 99%